2016
DOI: 10.5430/cns.v4n4p9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring experiences of fostering positive work environment in Norwegian nursing homes: A multi method study

Abstract: Objective: The aim of the study is to explore what characterizes the work culture in Norwegian nursing homes and what promotes the positive aspects in the work culture. Methods: Research design: Multimethod research. Two surveys (N = 105) and interviews with 11 informants at three Norwegian nursing homes were conducted. We included the questionnaires: The Systematizing Person-Group Relations, that seek to explore which aspects dominate the particular work environment identifying challenges, limitations and opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Prior to any formal innovation training, both groups (the participant and nonparticipant group) completed the questionnaire to determine each group's initial level of innovation understanding. It is suggested that a t test is an appropriate measure when distinguishing between two groups' innovative climate or perception of their innovative activity (André, Ringdal, Skjong, Rannestad, & Sjøvold, 2016). Accordingly, a t test was conducted to determine if there was any significant difference between either groups' innovation understanding prior to any training.…”
Section: Quantitative Datamentioning
confidence: 99%
“…Prior to any formal innovation training, both groups (the participant and nonparticipant group) completed the questionnaire to determine each group's initial level of innovation understanding. It is suggested that a t test is an appropriate measure when distinguishing between two groups' innovative climate or perception of their innovative activity (André, Ringdal, Skjong, Rannestad, & Sjøvold, 2016). Accordingly, a t test was conducted to determine if there was any significant difference between either groups' innovation understanding prior to any training.…”
Section: Quantitative Datamentioning
confidence: 99%
“…In overcome resistance interventions targeting the work environment must be inserted Employees in nursing homes (NH) are under strong pressure to provide good care to the patients (1,2). It is di cult to recruit and retain quali ed workers (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…It is di cult to recruit and retain quali ed workers (3,4). The focus on professional development and attitudes is therefore of great importance for NHs to appear as an attractive workplace for health professionals (1). Eldercare concept positions that municipalities need to properly poise their eldercare innovations into three key groups; improving the quality of care for the elderly, improving the working environment, and societal e ciency (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations